Meningocoxemic Septic Shock; A Case Report and Review of the Literature - Murat Özkale (Galenos Yayinevi, 2021)
Meningococcal infections that have high mortality and morbidity in childhood and progress rapidly are an important health problem. It is one of the most important emergent diseases of the infectious diseases. Neisseria meningitidis has 13 serogroups. A, B, C, Y and W135 are the most common cause of invasive diseases among these serogroups. The outcome of meningococcal disease is dependent on the immediate recognition of two major complications: Shock and increased intracranial pressure syndrome. Rapid recognition of the disease and these complications are very important for the outcome of affected patients with appropriate treatment. Our case is a 6-month-old girl who presented with fever, malaise and a rapidly spreading rash all over the body. Septic shock due to meningocoxemia was considered because of the typical rash, weakness, susceptibility to sleep and low blood pressure. This case report includes a review of septic shock therapy due to meningococemia in a patient who was diagnosed with invasive meningococcal disease and died despite rapid and appropriate treatment methods.